2022
DOI: 10.1002/jcla.24734
|View full text |Cite
|
Sign up to set email alerts
|

Detection of interstitial pneumonia with autoimmune features and idiopathic pulmonary fibrosis are enhanced by involvement of matrix metalloproteinases levels and clinical diagnosis

Abstract: Background: Higher detection of interstitial pneumonia with autoimmune features (IPAF), idiopathic pulmonary brosis (IPF) has signi cant diagnostic and therapeutic implications. Some MMPs have been reliable diagnostic biomarkers in IPAF and IPF in previous studies, yet relevant reliability remains to be recognized. Material and Methods: 36 ILD patients, including 31 IPAF patients (Mean ± SD, 50.20 ± 5.10 years; 16 (51.6%) females) and 5 IPF patients (Mean ± SD, 61.20 ± 6.73 years; 1 (20.0%) females) were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated that matrix metalloproteinases (MMPs), which are pivotal proteolytic enzymes, are involved in pathological and inflammatory processes in several respiratory diseases, such as interstitial pneumonia [237] , pulmonary fibrosis [238] , and COPD [239] . In particular, MMP-1, MMP-2, MMP-8, and TIMP-1 have been demonstrated in experimental and clinical research to influence inflammation [240] , [241] , [242] .…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that matrix metalloproteinases (MMPs), which are pivotal proteolytic enzymes, are involved in pathological and inflammatory processes in several respiratory diseases, such as interstitial pneumonia [237] , pulmonary fibrosis [238] , and COPD [239] . In particular, MMP-1, MMP-2, MMP-8, and TIMP-1 have been demonstrated in experimental and clinical research to influence inflammation [240] , [241] , [242] .…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%
“…In particular, MMP-1, MMP-2, MMP-8, and TIMP-1 have been demonstrated in experimental and clinical research to influence inflammation [240] , [241] , [242] . These factors may even be expected to become promising typical biomarkers to detect the severity of some lung diseases [238] . Ceylanlı et al [243] found that LA could suppress MMP-1, MMP-2, MMP-8, tissue inhibitors of metalloproteinase-1 (TIMP-1), TNF-α, IL-1, and MDA expression, thereby attenuating 5-fluorouracil (5-FU)-induced gastrointestinal mucositis in rats.…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%